2023
DOI: 10.3390/lubricants11060242
|View full text |Cite
|
Sign up to set email alerts
|

A Numerical Investigation of the Effects of Groove Texture on the Dynamics of a Water-Lubricated Bearing–Rotor System

Abstract: This paper aims to investigate the combined effects of working condition and structural parameters of groove texture on the dynamic characteristics, stability and unbalance response of a water-lubricated hydrodynamic bearing–rotor system to avoid instability and excessive vibration of the rotor. The Navier–Stokes equation, standard K-ε model with enhanced wall treatment and Zwart–Gerber–Belamri cavitation model are considered using the commercial software Fluent to calculate the stiffness and damping coefficie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Song et al [4] discussed the performance of gas bearings with spiral grooves on the surface, and found that the spiral groove improved the load capacity of bearings. Applying a numerical method, Feng et al [5] investigated the dynamics of a bearing-rotor system considering grooves of the bearing surface, and discovered that some kinds of grooves could improve the stability of the system. In addition to these studies on the surface grooves of bearings, there have been many statistical investigations on the structures of bearing surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…Song et al [4] discussed the performance of gas bearings with spiral grooves on the surface, and found that the spiral groove improved the load capacity of bearings. Applying a numerical method, Feng et al [5] investigated the dynamics of a bearing-rotor system considering grooves of the bearing surface, and discovered that some kinds of grooves could improve the stability of the system. In addition to these studies on the surface grooves of bearings, there have been many statistical investigations on the structures of bearing surfaces.…”
Section: Introductionmentioning
confidence: 99%